Citotoxicity and Genotoxicity Screening of some Aquatic Bodies in Shkodra Region Using Allium Cepa L. test - Kopliku, Ditika; Mesi, Anila; Golemi, Suzana (Richtmann Publishing, 2012)
The reaction of Allium cepa (L.) genetic material to the presence of potential cytotoxic and genotoxic substances in waterenvironment was used to screen the water toxicity presence and degree of Shkodra lake, Buna and Drini rivers, by measuring onionbulbs root length (MRL), Mitotic Index (MI), Phase Index (PI) and chromosome abnormalities (CA), grown in water samples fromShiroka, Zogaj, Shegan, Kamicë, Stërbeq, Buna bridge, Bahçellek, Zues and Dajç. All parameters were compared with filtered tap watercontrol, using χ2 test. Rating of samples for MRL and MI values was decreasingly: tap water, Stërbeq, Kamicë, Shiroka, Buna bridge,Zogaj, Bahçellek, Dajç, Zues, Shegan. Only the MRL and MI values of Dajç, Zues and Shegan were significant (p<0.05), compared totap water. Most frequent CA types were: stickiness, bridges and fragments. Rating of samples for CA was increasingly: tap water,Kamicë, Stërbeq, Buna Bridge, Shiroka, Dajç, Bahçellek, Zogaj, Shegan, Zues. The number of abnormal dividing cells was significant(p<0.05) in: Dajç, Bahçellek, Zogaj, Shegan, Zues. It was noticed high level of CA rate (genotoxity) in water sample of Zogaj, whichcould not be screened by cytotoxic examinations (MRL and MI). The results indicated a slight water pollution in Dajç, Shegan, Bahçellek,Zogaj and Zues samples, serving as a first alert of chemical pollution environmental impact, even in low concentrations. Deeper andlarger scaled monitoring network, using bioassays, has to be done in Shkodra region to protect ecosystems, biota and humans.